Pyomyositis caused by Salmonella enterica: a rare case report - Kumar, B. Vijay; Rao, G. Vamshi Nandan; Veena, M.; Sahu, Monalisa; Shivaram Rao, K. (International Journal of Research in Medical Sciences, 2026)
Pyomyositis is characterized as a primary bacterial infection of skeletal muscle, with Staphylococcus aureus being the most prevalent causative agent. In contrast, pyomyositis attributed to Salmonella enterica is an uncommon occurrence, typically observed in immunocompromised individuals, and often presents diagnostic challenges due to atypical laboratory findings. We report a such rare case involving an 82-year-old male who presented with severe bilateral thigh pain and difficulty in ambulation and a history of diabetes. He was admitted with provisional diagnosis of myositis. Laboratory evaluations indicated marked leukocytosis, elevated inflammatory markers, and hypoalbuminemia. These elevated inflamatory markers and MRI findings collectively suggested the possibility of pyomyositis with myonecrosis. Automated blood culture bactifast confirmed the presence of Salmonella enterica. In light of the diagnosis of pyomyositis caused by Salmonella enterica, prolonged intravenous antimicrobial therapy and supportive care were commenced. Following the appropriate administration of antibiotic treatment, the patient gradually exhibited symptomatic improvement and achieved hemodynamic stability. Early imaging and prompt initiation of aggressive antimicrobial therapy are essential for achieving favorable outcomes.